2015
DOI: 10.1021/am508973b
|View full text |Cite
|
Sign up to set email alerts
|

Steering the Efficiency of Carbon Nanotube–Silicon Photovoltaic Cells by Acid Vapor Exposure: A Real-Time Spectroscopic Tracking

Abstract: Hybrid carbon nanotube-silicon (CNT-Si) junctions have been investigated by angle resolved photoemission spectroscopy (AR-XPS) with the aim to clarify the effects of a nonstoichiometric silicon oxide buried interface on the overall cell efficiency. A complex silicon oxide interface has been clearly identified and its origin and role in the heterojunction have been probed by exposing the cells to hydrofluoric (HF) and nitric (HNO3) acid. Real-time monitoring of the cell efficiencies during the steps following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Indeed, the overall cell structure can be described as a FET, where the gate potential is represented by the built-in potential of the p-n heterojunction. It is important to recall that CNT-Si cells based on a p-type CNT bundle layer can be regarded as MIS944, as they can display a Si oxide layer at the interface between the CNT bundle layer and the n-Si. This justifies the choice to describe these junctions as a FET architecture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the overall cell structure can be described as a FET, where the gate potential is represented by the built-in potential of the p-n heterojunction. It is important to recall that CNT-Si cells based on a p-type CNT bundle layer can be regarded as MIS944, as they can display a Si oxide layer at the interface between the CNT bundle layer and the n-Si. This justifies the choice to describe these junctions as a FET architecture.…”
Section: Resultsmentioning
confidence: 99%
“…As the present PV devices are usually described in a MIS scheme944, V OC (Equation 2) can be expressed6162 as:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For understanding the operation mechanism, a combination of suitable spectroscopic tools has been used recently [39]: AR-XPS for a direct probe of the buried oxide interface, Raman spectroscopy to obtain information on CNT properties, and the acquisition of current density-voltage (J-V) characteristics for monitoring the behavior of the photovoltaic device after exposure to acid.…”
Section: Cnts For Photovoltaic Applicationsmentioning
confidence: 99%
“…According to previous studies, introducing functional materials into the CNT‐Si solar cells has proved to be an effective strategy to improve the cell efficiency. To this end, a variety of materials, such as acids, metallocenes, Au nanodots, AuCl 3 , colloidal TiO 2, polymethylmethacrylate, MoO x , and CuCl 2 /Cu(OH) 2 , have been explored, whose functions generally fall into three categories, including 1) chemical doping; 2) antireflection; and 3) acting as functional layers. For example, it was found that those introduced materials could dope CNTs and modulate the work function of CNTs as well as the diode/junction characteristics (e.g., for HNO 3 and Au salt) or act as an antireflection layer to enhance the light absorption and external quantum efficiency (e.g., for TiO 2 and polymethylmethacrylate) .…”
Section: Introductionmentioning
confidence: 99%